What Influence did British Women Arabists Have on the Anglo-Arab relationship in the Middle East (1914-45)? - ALISON PRICE (2023)
My meeting in Kuwait, in 1984, with 88-year-old Dame Violet Dickson, Umm Kuwait, began a quest to expand my world-view of the region that would be my home for forty years. My research led to the discovery of a network of British women who had travelled through, lived, worked and even died in the Middle East in the nineteenth- and early twentieth- centuries. I was intrigued by the roles played by such women in a time when imperial Britain, a former trade partner of the Ottomans, had increased its political influence in the region after WW1. Post-colonial discourse today describes the period as imperial ‘colonisation’, ‘occupation’ and ‘invasion’ with the narrative focussing upon the male British key-players (administrators, politicians and military personnel) being opposed by Arab nationalists. This thesis will argue that the women under consideration were not part of the ‘imperial machine’ and their influence, within their given circumstances, was directed towards supporting Arabself-determination and survival.It will show that their personal identities, albeit individual, were the hybrids of imperial, national, gender and cultural identities. These evolved through independent travel and cross-cultural communication, into an alternative British persona (one which has been overlooked by the current academic scholarship). To consider each woman separately is to exceptionalise and easily dismiss her as an anomaly, therefore this thesis has created a collective of British women Arabists to demonstrate that, although they were not the norm, they were representatives of the extraordinary women of their space and time and must be included without bias in the ‘colonial’ discourse. This thesis will demonstrate that women Arabists acted through the ideals of liberalism and in their official positions in support of the self-determination and well-being of the Arab people.Their humanism has left positive legacies remembered today in the Middle East and yet their histories are absent in the current summary of British imperialism in the region. Thus this thesis opens a new discussion for British anti-imperialists existing in the Middle East during that period. The four Case Studies cover the period from the decline of the Sultanate of the Ottoman Empire, the rise of the Ottoman Committee for Union & Progress, World War 1, interwar years and World War 2. This thesis builds on extensive research, using Western and Arab academic, primary and secondary sources. The focus is upon the evolution, work, international thought and influence of Gertrude Lowthian Bell CBE (Case Study 1), Dame Violet Dickson (Case Study 2), Dame Freya Stark (Case Study 3) and Doreen Ingrams (Case Study 4) in the Middle East.